Funciones desempeñadas como asesora de negocios en Credichavin (2014-2016) y en MiBanco (2016-2017) - Zamora Salas, Vania Magaly (2018)
The main objective of this Professional Sufficiency Work is to publicize the work I did as Business Advisor in CrediChavín and in Mibanco during the period (2014- 2017), financial entities oriented to lend money to the MYPES, as well as to the medium-sized companies that are currently the driving forces of our country's progress and development. That is to say, the Business Advisor of a financial institution, has as his axis objetive, the placement and careful management of the money entrusted to him by the financial entity, ensuring that both, the financial institution and the client, obtain utility for the use of the money. For this, you need to have technical resources, logistics and skills that will facilitate you to meet this objective; such as Accounting, Financial Mathematics, Professional Ethics, Sales, empathy, sales technique, etc. Secondary objectives are those that contribute to the achievement of the principal; such as the daily elaboration of the work plan, the visits and telephone calls to the clients, both old and new, to offer the new and promotional products of the company; This is how the Business Advisor contributes decisively to the development of the Country. All these activities are carried out within the regulations of the financial companies, which in turn operate under the SBS, that is, the deductive as well as the inductive methodology has been used. The achievements or results have been positive: growth both in the number of clients and in placements, that is, in the amount placed, and decrease in arrears in recoveries. The present work will be very useful for those who want to get oriented to this work area.